The Biocontrol Functions of Bacillus velezensis Strain Bv-25 Against Meloidogyne incognita - Tian, Xue-liang; Zhao, Xiao-man; Zhao, Song-yu; Zhao, Jian-long; Mao, Zhen-chuan (Frontiers in Microbiology, 2022)
Meloidogyne incognita is obligate parasitic nematode with a wide variety of hosts that causes huge economic losses every year. In an effort to identify novel bacterial biocontrols against M. incognita, the nematicidal activity of Bacillus velezensis strain Bv-25 obtained from cucumber rhizosphere soil was measured. Strain Bv-25 could inhibit the egg hatching of M. incognita and had strong nematicidal activity, with the mortality rate of second-stage M. incognita juveniles (J2s) at 100% within 12 h of exposure to Bv-25 fermentation broth. The M. incognita genes ord-1, mpk-1, and flp-18 were suppressed by Bv-25 fumigation treatment after 48 h. Strain Bv-25 could colonize cucumber roots, with 5.94 × 107 colony-forming units/g attached within 24 h, effectively reducing the infection rate with J2s by 98.6%. The bacteria up-regulated the expression levels of cucumber defense response genes pr1, pr3, and lox1 and induced resistance to M. incognita in split-root trials. Potted trials showed that Bv-25 reduced cucumber root knots by 73.8%. The field experiment demonstrated that disease index was reduced by 61.6%, cucumber height increased by 14.4%, and yield increased by 36.5% in Bv-25–treated plants compared with control. To summarize, B. velezensis strain Bv-25 strain has good potential to control root-knot nematodes both when colonizing the plant roots and through its volatile compounds.